From Notes to Knowledge: A Comprehensive Review of Early Childhood Music Education - Zhou, Huanran (Transactions on Social Science, Education and Humanities Research, 2024)
Music education is widely acknowledged as a valuable instrument for fostering young children's creativity and development. Through a comprehensive literature review, this study evaluates various teaching methods, including the Carabo Cone, Dalcroze, Suzuki, Kodaly, and Orff methods. The study also examined external and internal factors that affect music education, such as the learning environment, parental engagement, and teacher influence. Although significant benefits were shown, the study fell short in distinguishing between three different areas (vocal, instrumental, and movement) of music education, as well as in addressing development between the ages of 0 and 6. This article encourages broadening the scope of research beyond Western music to include ethnic and world musics, as well as conducting additional empirical research to validate the benefits of music education in different dimensions. This article serves as an introduction guide for future instructors and lays the groundwork for future scholarly research into the various effects of early childhood music education.